The Drosophila tom retrotransposon encodes an envelope protein. - Tanda, S (1994)
The tom transposable element of Drosophila ananassae is mobilized with high frequency in the germ line of females from the ca; px strain, and its insertion results in mutations that show almost exclusively dominant eye phenotypes. tom is a long terminal repeat-containing retrotransposon that encodes three different open reading frames (ORFs). It is expressed in the nurse cells during oogenesis, in the central and peripheral nervous systems during embryonic development, and in the imaginal discs of the larva. tom RNA accumulates in the germarium of ovaries from ca; px females but not in the parental inactive strain, suggesting that this altered pattern of tom expression might be the cause of the high rate of mobilization of this retrotransposon. The specificity of tom-induced eye phenotypes can be explained by the presence of regulatory sequences responsible for expression of tom in the eye imaginal discs of third-instar larvae. These sequences might cause overexpression of adjacent genes affected by tom-induced mutations, resulting in the death of undifferentiated cells located anterior to the morphogenetic furrow. In addition to the full-length RNA, tom is also transcribed into a spliced subgenomic transcript that encodes a protein resulting from the fusion between the amino-terminal region of the first (gag) and the third ORFs. The protein encoded by this RNA shows structural characteristics such as a signal peptide, glycosylation sites, endopeptidase cleavage site, and fusion peptide that are typical of the envelope proteins of retroviruses. Antibodies against tom ORF3 recognize two different proteins present in female ovaries, suggesting that tom might be able to form infective viral particles that could play a role in the horizontal transmission of this retrotransposon.